Understanding the role of oral and vaginal microbiomes in HPV-related cervical, head, and neck cancers: knowledge gaps and feasibility in Sub-Saharan Africa - Kamassa, Hélène Eya; Katawa, Gnatoulma; Isawumi, Abiola; Olwal, Charles; Gbewonyo, Winfried Seth; Quashie, Peter Kojo; Bediako, Yaw (Frontiers in Microbiomes, 2025)
Microbiome dysbiosis, characterized by an imbalance in the composition of microbial communities, has emerged as a potential risk factor for the development of cervical, head, and neck cancers. While previous studies have predominantly focused on high-income countries, there is a significant gap in understanding the relationship between microbiome alterations and cancer development in sub-Saharan Africa. Considering the unique socio-economic and environmental factors in this region, investigating the role of vaginal and oral microbiota in the progression of these cancers is crucial. This review explores the involvement of microbial dysbiosis in cervical, head, and neck cancers, particularly how it influences Human Papillomavirus-driven immune evasion, and highlights the importance of microbiota profiling in sub-Saharan Africa. The implications of these insights for cancer prevention and treatment strategies in this population are also discussed.